Hasil Work Engagement dari Work Life Balance karyawan: Peran Mediasi Job Crafting - noerchoidah noerchoidah; Ratih Indriyani (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background - Competition between companies is very competitive to be the best organization must manage human resources and pay serious attention to the behavior, attitudes, and psychological state of employees. The company is expected to only employ competent human resources with a positive work attitude. However, the work-life balance of employees in hotels has not been felt evenly by hotel employees in Surabaya. Therefore, it is necessary to study the factors of work-life balance and work engagement by mediating job crafting for hotel employees in Surabaya. Objectives - To provide empirical evidence related to the direct effect of work-life balance on work engagement, and the indirect effect of using job crafting mediation on hotel employees in Surabaya. Design/method/approach - Quantitative research that is explanatory research is used in this study. A total of 152 hotel employees in Surabaya were used as samples using the purposive sampling technique. The data that has been collected and tabulated is then analyzed using the PLS program. Findings - This study provides evidence that work-life balance has a significant effect on job crafting, work-life balance does not affect work engagement. After that, job crafting influences work engagement. Furthermore, job crafting has a fully mediating role in work-life balance and work engagement. Conclusion - Work life balance can improve work engagement. job crafting is able to mediate between work life balance and work engagement of hotel employees in Surabaya. work life balance allows employees to build a balance between work and family roles. Research Implications - Hospitality management needs to increase work engagement which is much needed for employees in completing their job responsibilities to be better and give their best contribution in achieving organizational goals. Paying attention to the work-life balance of employees between work and family makes employees happy so they are motivated to give their best performance in providing services to hotel guests satisfactorily. Provide support by facilitating employee job crafting to modify the way of working according to the needs of the job. Research Limitations - This research is not free from limitations. This study only examines hotel employees in Surabaya, so further research needs to be carried out in different sectors that have different characteristics. The results of the study which were found to be insignificant between work-life balance and work engagement need further empirical evidence. In addition, it is necessary to further develop factors that affect work engagement, such as work stress and psychological contracts.